ANALISIS KINERJA PENDAPATAN ASLI DAERAH KOTA PONTIANAK TAHUN 2007-2015 - SUSANTI B11212094 (Universitas Tanjungpura, 2017)
To finance the development, one of the efforts of Local Government is to absorb the funds of loccally generated revenues, which consist of Local Taxes, Levies, Regional Wealth Management Results and other legal local revenues as beneficial in improving the local income and encouraging the growth rate of regional economy. This research aims to determine the development of the sources of locally generated revenues to the locally generated revenues of Pontianak city, determine the contribution of the sources of locally generated revenue, and determine the effectiveness of imposing Local Revenue conducted by the Regional Government of Pontianak City. This research used a descriptive analysis to determine the development of the sources of locally generated revenues of Pontianak city from 2007 to 2015. The results show that the development of Local Tax is constantly increasing while Retribution, Regional Wealth Management and other Regional and Local Revenues experienced fluctuations in growth. The results of contribution analysis indicated that the contribution of Local Taxes was an average of 67.40% per year which was the most dominant of the Local Revenue, and the smallest contribution was 2.17% which was contributed by the separated Regional Wealth Management. The effectiveness of the collection of all the sources of local revenues have been effective, with an average score of 91.97%, almost reaching the target. Keywords: Locally generated revenue, Local Taxes, Levies, separeted Regional Wealth Management and Other Legal Local Revenues.